(untitled) (Journal of Global Accounting, 2023)
The aim of this study is to examine the effect of accounting information on the sustainable growth of listed industrial goods firms in Nigeria. The study among others intends to determine the effect of sales volume on the sustainable growth (Tobin’s ‘Q’) of listed industrial goods firm in Nigeria and to ascertain the effect of net profit (profit after tax) on the sustainable growth (Tobin’s ‘Q’) of listed industrial goods firm in Nigeria. The work employed multiple regression model to test the null hypothesis and purposive sampling technique to analyze the audited financial statements of seven (7) listed industrial goods firms that were used in the study for the period of 2011 – 2020. Based on the findings, the study recommends that managers of listed industrial goods firms in Nigeria should seek for better ways to improve their sales performance and profitability since it can also be seen as an indicator of firm’s success. In other words, there is a weak association between accounting information and the sustainable growth of firms when measured by Tobin’s Q.